Anticancer activity of cloned Nisin as an alternative therapy for MCF-7 brest cancer cell line: Anticancer activity of cloned Nisin for MCF-7 brest cancer cell line - Said Taha Said Ahmed, Samann; Abdulrahman, Zirak Faqe Ahmed; Othman, Ramadhan Tayeb (Cellular and Molecular Biology, 2023)
Despite advancements in treatment and detection, cancer remains one of the most common causes of death worldwide. Conventional chemotherapeutic drugs used to treat cancer have non-specific toxicity toward normal body cells, which leads to several adverse effects. Second, malignancies are known to develop resistance to chemotherapy over time. As a result, the demand for novel anticancer drugs is growing daily. The most frequent type of cancer among women is breast cancer. Utilizing cloned Nisin as an anticancer was the purpose of this study using Gibson cloning and a cell-free peptide synthesis system, then purification of the target protein. The antiproliferative effect of Nisin against a breast cancer MCF-7 cell line was also determined using an MTT assay, and viability in cell lines was measured using acridine orange and propidium iodide. Our findings demonstrate the successful isolation and cloning of the NisA, gene in addition to inducing of peptide synthesis system and then purification of a target protein. MTT assay results indicate that Nisin exhibits a high and selective cytotoxicity against the MCF-7 cell line with an IC50 value of 11.68 μg/ml. This data suggest that the NisA gene had in vitro antiproliferative effect against breast cancer cell. However, more research, including a combination of the NisA gene with other anticancer therapy in clinical use. In addition, in vivo studies are required.